Determining the load on a container with a truss frame during railroad transportation - Lovska, Alyona; Zharova, Oksana; Muradian, Arsen; Kyryllova, Valeriia; Pelypenko, Yevhen (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the processes of perception and redistribution of loads in the structure of a container with a truss frame during railroad transportation. The task addressed is to ensure the strength of the container walls under operational loads. To provide for the strength of the container walls, it is proposed to increase the rigidity of the frame. In this case, it is assumed to install braces between the corner and vertical posts, as well as a reinforcing horizontal belt between the vertical posts. To substantiate the proposed improvement, a calculation of the container strength was performed. Two modes of its loading were taken into account: lateral loading and vertical loading. The calculation results showed that the stresses in the container structure under the considered loading modes do not exceed the permissible ones. At the same time, the maximum stresses when the container perceives lateral loads are almost 12% lower than those that operate in a typical structure, and when perceiving vertical loads – by 5%. In addition, a modal analysis of the container was performed as part of the study. The results of the calculation showed that the safety of its transportation from the point of view of modal analysis is observed. A feature of the results of this study is that ensuring the strength of the container is achieved not by using high-cost materials in its design but by introducing truss components into the frame. The scope of practical application of the research results is railroad transport. The conditions for practical use of the results are the fabrication of truss components from the same material as the container frame. The results of the study could also contribute to compiling the recommendations for the design of new and modernization of existing containers